The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s00223-004-0096-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: A Necessity for Children and Adolescents in Greece

Abstract: Children and adolescents with the high bone turnover comprise a high risk population for vitamin D insufficiency. A sample of 178 clinically healthy children aged 3 to 18 years who came from public schools and lived in North West of Greece participated in the study. They were grouped into three age groups (I: 3-10, II: 11-14 and III: 15-18 years of age). Blood samples were taken during winter and summer months for determining calciotropic hormones, calcium, phosphate and biochemical markers of bone synthesis.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 60 publications
9
37
2
4
Order By: Relevance
“…In our study, no significant difference was found between the patient and control groups in terms of vitamin D level. However, the rates of vitamin D deficiency and insufficiency in both groups were found to be higher compared to the studies conducted in our country and in the world (8,10,13,14).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In our study, no significant difference was found between the patient and control groups in terms of vitamin D level. However, the rates of vitamin D deficiency and insufficiency in both groups were found to be higher compared to the studies conducted in our country and in the world (8,10,13,14).…”
Section: Discussioncontrasting
confidence: 78%
“…In children, vitamin D deficiency and insufficiency are important health problems and variable prevalences have been reported in studies conducted in many countries (8)(9)(10)(11). In a study conducted in Greece, vitamin D deficiency was found with a rate of 14% in children aged between three and 18 years (8).…”
Section: Discussionmentioning
confidence: 99%
“…(9,16,21) Other reports, including this one, show similarly high frequencies in European countries located at lower latitudes, namely, France (41%), but also Greece, (20) Germany, (26) and Switzerland. (19) The prevalence of low 25(OH)D levels during the winter is even higher when using the 40 nmol/L cutoff (61% in this study).…”
Section: Discussionsupporting
confidence: 58%
“…(13) Serum 25(OH)D levels are considered the best marker of vitamin D status and have been used commonly to assess the prevalence of vitamin D deficiency/insufficiency in healthy children and adolescents. (9,10,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) However, a clear understanding of the biologic significance of given concentrations of circulating 25(OH)D is still lacking, and reference ranges for vitamin D are being reassessed on the basis of what constitutes a normal concentration compared with optimal concentrations. (27)(28)(29) Most clinicians agree that serum 25(OH)D levels below 25 to 30 nmol/L (10 to 12 ng/mL) may lead to nutritional rickets, hypocalcemic convulsions, dental problems, and poor growth in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Vitamin D is found in inactive form in body which is converted to active vitamin D by sun rays. [4][5] Vitamin D deficiency is common in India; moreover tendency to cover the skin to avoid pigmentation may lead to deficiency of vitamin D. [6][7][8] Vitamin D have various other important functions like cellular differentiation and replication in many tissue and organs, including metabolism of calcium. [9,10] Vitamin D is considered very important for insulin secretion and sustain the normal glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%